Muscat in Rural Tanzania: Omani Arabs, Identity, and Citizenship in Post-Slavery Tanzania, 1920s–1960s - Nyanto, Salvatory S.; Becker, Felicitas M. (African Historical Review, 2025)
Studies on post-slavery in East Africa often concentrate on the aftermath of slavery for the formerly enslaved. By contrast, former owners’ experiences after abolition and during emancipation are rarely explored. This article examines the trajectories of Omani Arabs in western Tanzania during and after the end of slavery, ca. 1910 to the late twentieth century. Having settled and built slavelabour plantations along the central caravan route in the nineteenth century, they relocated to rural areas between the 1920s and 1930s following the legal abolition of slavery and great economic depression. To tell their story in postslavery Tanzania, we drew examples from primary sources deposited in the archives of Tanzania and the United Kingdom, and oral interviews collected from the many villages in rural western Tanzania where the Omanis’ descendants now live. We show that the history of the Omani Arabs and their identity in twentieth-century western Tanzania was shaped by economic dispossession and uncertainty about citizenship, but also by evolving cultural identities and sustained social networking.
Keywords: Relations – Oman – Zanzibar

Sayyid Barghash et sayyid Abdulaziz, de l’exil à Bombay au trône de Zanzibar - Belhacel, Abdelhakim (Outre-Mers, 2024)
Les premiers exils de souverains est-africains en Asie du XIXe siècle sont le fait du dirigeant omanais de Zanzibar sayyid Saʿīd (r. 1806-1856). Ses domaines s’étendent à de larges pans du golfe Persique et de l’Afrique de l’Est et il exile des vassaux remuants à Mascate. Peu de temps après sa mort, ce sont deux de ses fils qui sont à leur tour victimes de cette pratique, cette fois-ci du fait des Britanniques. Sayyid Barġaš et sayyid ʿAbdulʿazīz sont alors exilés à Bombay et ne sont autorisés à quitter la ville qu’au bout de deux ans. Cet article vise à étudier le contexte de cet exil, enjeu autant que résultat d’une guerre civile à Zanzibar. L’historiographie a insisté sur l’influence, réelle ou supposée, qu’a eu sur Barġaš son séjour contraint en Inde d’où il aurait rapporté à Zanzibar techniques, architecture… Cet article examine ces transferts et les modalités de cet exil, notamment son financement. Il vise également à mettre en lumière le caractère ambigu de cet exil, entre bannissement et exil choisi, et à montrer comment il est instrumentalisé tant par les Britanniques que par les princes omanais.
Keywords: Relations – Oman – Zanzibar; Relations – Zanzibar – Royaume-Uni; Vie politique – Zanzibar – 1806-1856; Vie politique – Zanzibar – 1856-1870

Society of the Righteous Ibadhi Muslim :Identity and Transnationalism in Tanzania - Wortmann, Kimberly T. (Indiana University Press, 2024)
Although the rule of the Omani sultanate in Tanzania came to an end following the Zanzibar Revolution in 1964, the legacy of its empire still exists today, along with its distinctive religious identity. The Ibadhi Muslims of Omani descent, who are neither Sunni nor Shi'a, have used a message of tolerance and harmonious coexistence to spread their beliefs across North and East Africa in a post-revolution and post-independence era. In Society of the Righteous, Kimberly T. Wortmann explores how the Ibadhi-Omani community in Tanzania has engaged in charitable activities, cooperation within the Muslim community, and economic development, despite facing suspicions of foreign influence and elitism. The focus is on the Istiqaama Muslim Community, an international charity network established in Oman and Tanzania in 1995. This ethnographic and transregional study documents the strategies employed by the "People of Truth and Righteousness" to preserve their unique religious practices and beliefs. Society of the Righteous moves beyond the typical discussions on global Muslim religion and politics, such as tradition versus modernity, conflicts between different branches of Islam, and the global war on terror. Instead, it explores the intricacies of a religious community whose significance has been obscured by the limitations of area studies paradigms. It illuminates the complexities of religious identity, transnational networks, gender relations, and the power of collective memory in shaping narratives of belonging, cultural preservation, and change in an increasingly interconnected world.
Keywords: Relations – Oman – Zanzibar; Relations – Zanzibar – Mzab; Tolérance religieuse – Zanzibar